The effectiveness of a communication enhancement program for rehabilitating drug dependents - Jose, Maria Teresa D. (Animo Repository, 2005)
The study sought to determine the effectiveness of a therapeutic training program for rehabilitating drug dependents. Purposive sampling was used involving twenty rehabilitating drug dependents confined at the NARCOM Treatment and Rehabilitation Center at Bicutan, Taguig, Metro Manila. All participants volunteered for the program and met the minimum requirements set regarding their educational background, intelligence quotient, and, communication skills. They, too, had to be regularly visited by their relatives. The study used the pretest-posttest- delayed posttest control group design. Participants were grouped at random and the Interpersonal Communication Inventory test instrument was administered to all group members at specified intervals. The experimental group was subjected to a Communication Enhancement Program (CEP) and underwent counseling sessions a month thereafter. Wilcoxon's Matched-Pairs Signed Ranks Test was used to determine differences within the experimental and control groups across three testing periods. A significant difference was noted only between the experimental group's pretest and delayed posttest scores. Results showed that the CEP was significantly effective for the experimental group, but that such effect took place one month after treatment.